Color Brightness and Growth Levels of Goldfish (Carassius auratus) Reared with Different Light Spectrums - Sabrina, Annisa Nur; Mukti, Akhmad Taufiq; Suciyono, Suciyono; Kenconojati, Hapsari; Ulkhaq, Mohammad Faizal; Fasya, Arif Habib; Lamadi, Arafik; Imlani, Ainulyakin; Mariah, Sharven Rao (Universitas Airlangga, 2023)
Carassius auratus is one of the potential ornamental freshwater fish in Indonesia. The potential of this fish increases along with the dominance of the colors produced during cultivation. We have demonstrated to treat differences in the light spectrum to increase the brightness of the colors. Completely randomized design with 5 treatments and 4 replications as the design i.e., (P1) negative control with no LED, (P2) positive control using white LED light and a room light intensity, (P3) red LED, (P4) green LED, and (P5) blue LED. We reported that the red LED was the light spectrum that produced the best treatment to increase the color brightness and growth of goldfish. The brightness level of the color in the P3 treatment was 63,04% as measured by Adobe Photoshop; using the M-TCF method, it was 8,94% body color, 9,37% dorsal fin, and 9,31% tail fin. Meanwhile, the best specific growth rate were found in P5 followed by P3 treatment in a row of 5,33 ± 0,66b, 3,46 ± 0,57ab, respectively. The red color spectrum produced the best pigmentation but the blue color spectrum was the best for the growth of C. auratus.